THE EUROPEAN PRINCIPLES OF UKRAINE-NATO RECIPROCAL RELATIONS AND THE STUDYING OF EXPERIENCE OF NEUTRALITY IN FOREIGN AFFAIRS OF SEPARATE STATES - Volkovich, O. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2020)
The article considers European principles of reciprocal relations between Ukraine and NATO and scrutinizing the experience of neutrality of foreign relations of separate states generating and generalizing the fundamental principles on settlement and exit from the Russian-Ukrainian military conflict. The attention has also been stipulated on the peculiarities on obtaining neutrality by European states, scrutinizing the experience of separate countries towards settlement of external conflicts (Sweden, Finland). The government of Sweden has determined a new defense policy, related with the non-participation in wars, loses its practical content and the neutral status of the mentioned countries to a certain extent becomes a symbolic consequence of historic traditions. The separate issues of fundamental principles of the development of relations between Ukraine and NATO have been scrutinized.There’s a new tendency visible in the foreign policy of states – unlike the previous periods of time the neutral and non-bloc states do not avoid nor open the international political, economic and even military cooperation, they cooperate within the framework of UN, NATO, EU, OSCE hoping that this cooperation will facilitate the reinforcement of friendly relations between states.Ukraine is presented as a sovereign, independent and stabile state, that is irreversibly loyal to the principles of democracy and the rule of law, has a prior meaning for the Euro-Atlantic security. The relations between Ukraine and NATO started the development at the beginning of the 90-ties of the XX century and since then has become one of the most significant NATO partnerships. In the course of 2010 in Ukraine there was a tendency of measures and events predominantly related with the review of organizational principles of cooperation with NATO and the transformation of entities responsible for this process. Starting from 2014, because of the Russian-Ukrainian conflict, the Ukraine-NATO cooperation has been intensified in a set of critical fields. Also, a step that has not been less significant was the event that on 12 of June 2020 the NATO North Atlantic Council has approved the decision on granting our state the status of a NATO partner-nation with extended capabilities.
Keywords: reciprocal relations, neutrality, military conflict, principles, NATO, EU, security